1999
DOI: 10.1111/j.1744-6570.1999.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits, General Mental Ability, and Career Success Across the Life Span

Abstract: The present study investigated the relationship of traits from the 5factor model of personality (often termed the "Big Five") and general mental ability with career success. Career success was argued to be comprised of intrinsic success (job satisfaction) and extrinsic success (income and occupational status) dimensions. Data were obtained from the Intergenerational Studies, a set of 3 studies that followed participantsfrom early childhood to retirement. The most general findings were that conscientiousness po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
1,346
15
80

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,655 publications
(1,562 citation statements)
references
References 98 publications
66
1,346
15
80
Order By: Relevance
“…Tett et al (1991) found that, in a meta-analysis, neuroticism was adversely correlated with job performance. Later research has confirmed this finding; for example, individuals high in neuroticism have significantly lower earnings (Gelissen and de Graaf 2006;Judge et al 1999;Sutin et al 2009). …”
Section: Personality and Workmentioning
confidence: 85%
See 3 more Smart Citations
“…Tett et al (1991) found that, in a meta-analysis, neuroticism was adversely correlated with job performance. Later research has confirmed this finding; for example, individuals high in neuroticism have significantly lower earnings (Gelissen and de Graaf 2006;Judge et al 1999;Sutin et al 2009). …”
Section: Personality and Workmentioning
confidence: 85%
“…Research shows that personality is correlated with jobrelated factors such as job performance (Judge et al 1999) and career choice (Page et al 2008). Hence, personality could also be correlated with the timing of retirement and the pathways towards retirement because more successful and more satisfied workers are likely to retire later than those who are less successful and less satisfied with their work.…”
Section: Personality and Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who score high for this factor are considered to be more self‐controlled and motivated. Conscientiousness is also associated with academic and vocational success (Judge, Higgins, Thoresen, & Barrick, 1999; Noftle & Robins, 2007; O'Connor & Paunonen, 2007). Our results showed that conscientiousness was negatively correlated with the L p in dlPFC, which plays an essential role in executive function.…”
Section: Discussionmentioning
confidence: 99%